Quantitative estimation of (-)-hinokinin, a trypanosomicidal marker in Piper cubeba, and some of its commercial formulations using HPLC-PDA - Kothapalli Haribabu; Makula Ajitha; Uppuluri Venkata Mallavadhani (Journal of Pharmaceutical Analysis, 2015)
The fruits of Piper cubeba have been used in Ayurvedic system of medicine for pain, tastelessness, painful urination and mouth diseases. Among its various chemical constituents, (-)-hinokinin, a trypanosomicidal dibenzylbutyrolactone lignan, is found in significant quantities. For quality evaluation of P. cubeba fruit and its commercial formulations, there is an urgent need to develop an analytical method based on (-)-hinokinin. For this purpose, an HPLC method was developed using photo diode array detector and Waters HR C18 column with gradient elution consisting of water and acetonitrile. The developed method was validated as per ICH-Q2B guidelines and found to be accurate, precise and linear over a wide range of concentrations (5â300Â Âµg/mL). (-)-Hinokinin contents were found to be in the range of 0.005â0.109%Â (m/m) in various P. cubeba samples. The developed method was extended to LCâMS for further identification and characterization of (-)-hinokinin in samples. The developed method is simple, rapid and specific, and can be used as a tool for quality control of P. cubeba fruits and its commercial formulations. Keywords: Piper cubeba, (-)-Hinokinin, HPLC, Quality control, Herbal formulations